2 Mental wellbeing in elite male under 23 soccer players: a team case study. (December 2018) - Richardson, Andy; Clifford, Tom; Abbott, Will; E Brownlee, Thomas; D Harper, Liam; J Naughton, Robert
Abstract : Recent research suggests a high prevalence of mental health disorders in professional soccer players, including symptoms of anxiety, depression, distress and adverse eating behaviours. Whilst a limited number of studies address this issue, the existing evidence is alarming and highlights a need for further investigations to develop a better understanding of the causes and consequences of mental health problems in professional soccer players. Thus, the aim of this study was to examine the influence of physical and emotional stressors on mental wellbeing (MW) in professional male soccer players. Using a longitudinal design, twenty-five male soccer players from the under 23 squad playing in the Premier League 2 division in the UK completed the Warwick-Edinburgh Mental Well-being Scale (WEMWBS) each week of the 2017/2018 season (37 weeks in total). Independent predictor variables of MW were injury, match selection (in the match squad), weekly training load (sum of total duration, total distance and total sprint distance) and win rate. Mean MW scores were calculated across the season for each player with a squad mean of 48±3.94, which is below the England population norm of 51.6. Mean MW was significantly lower when injured vs. not-injured (43.6±5.0 vs 49.9±3.5; p=0.01), but was not affected by selection, training load or match result. Multivariate regression models showed time out with injury to have the strongest influence on MW (r 2 =0.40, p<0.01), with longer periods of injury linked to lower MW scores. Matchday selection was the only other statistically significant variable, with a positive correlation between MW and selection (r 2 =0.23, p=0.02). Whilst elucidating the mechanisms by which time out with injury may affect MW was beyond the scope of this study, the association between injury and reduced MW highlights a need for mental health and wellbeing monitoring in injured soccer players. This could facilitate interventions and support to ensure health and performance are not negatively affected.